2020
DOI: 10.1111/cpr.12907
|View full text |Cite|
|
Sign up to set email alerts
|

Interleukin‐4‐loaded hydrogel scaffold regulates macrophages polarization to promote bone mesenchymal stem cells osteogenic differentiation via TGF‐β1/Smad pathway for repair of bone defect

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Therefore, great efforts are currently being addressed to design immunomodulatory and, at the same time, pro-osteogenic scaffolds capable of regulating and boosting the switch of M1 macrophages to M2 phenotype. The use of pro-osteogenic scaffolds carrying immunomodulatory molecules such as ILs or micro ribonucleic acids (microRNAs) [ 129 , 130 ] or the modulation of surface topographical cues of the scaffolds [ 131 ] are among the strategies currently being used to improve the bone healing facilitated by endogenous macrophages.…”
Section: Strategies Promoting Bone Healing Through An Endogenous Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, great efforts are currently being addressed to design immunomodulatory and, at the same time, pro-osteogenic scaffolds capable of regulating and boosting the switch of M1 macrophages to M2 phenotype. The use of pro-osteogenic scaffolds carrying immunomodulatory molecules such as ILs or micro ribonucleic acids (microRNAs) [ 129 , 130 ] or the modulation of surface topographical cues of the scaffolds [ 131 ] are among the strategies currently being used to improve the bone healing facilitated by endogenous macrophages.…”
Section: Strategies Promoting Bone Healing Through An Endogenous Responsementioning
confidence: 99%
“…The combined use of a wide range of pro-osteogenic scaffolds such as decellularized bone matrix, bi-layer hydrogel-porous scaffolds, and calcium-enriched hydrogels [ 129 , 132 , 133 ] loaded with IL-4, a key anti-inflammatory cytokine secreted by M2 macrophages, is now being explored as a promising strategy for repair of bone defects [ 129 , 133 ]. Interestingly, calcium-enriched hydrogels loaded with IL-4 showed superior in vitro and in vivo abilities in inducing both M2 macrophages polarization and MSCs osteogenesis by enhancing TGF-β1/Smad pathway.…”
Section: Strategies Promoting Bone Healing Through An Endogenous Responsementioning
confidence: 99%
“…Among these cytokines, IL-4 is widely studied, as it polarizes macrophages into an anti-inflammatory phenotype and inhibits LPS-induced pro-inflammatory cytokine synthesis [ 6 , 7 , 8 , 9 ]. Several prominent studies incorporated IL-4 into the scaffold and relied on its controlled release to modulate inflammation [ 10 , 11 , 12 , 13 , 14 ]. Yet, these studies and many others in the literature largely ignored the inflammatory environment at the injury site and its deleterious effects on immunomodulatory scaffolds, including the scaffold degradation rate and cytokine release profile.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, upregulation of M2 macrophages in fracture calluses by in situ application of IL-4 and IL-13 results in enhanced fracture healing (Schlundt et al, 2018). Correspondingly, a study by Zhang et al (2018) on human patients has determined a positive correlation between the percentage of M2 macrophages in clavicle fracture calluses and the rate of bone healing.…”
Section: M2 Macrophage Upregulation Is Essential During Bone Regeneration and Precedes Osteoinduction By Calcium Phosphate In Vivomentioning
confidence: 97%
“…In the context of biomaterials, augmenting the number of M2 macrophages during bone repair with various implants has been consistently linked to enhanced bone formation. For example, loading of different implant materials with IL-4, leading to M2 macrophage upregulation, results in enhanced bone defect regeneration or implant osseointegration (Hachim et al, 2017;Zhang et al, 2020;Zhao et al, 2021;. Moreover, Mahon et al (2020) and Yang et al (2021) also showed that M2 macrophage activation by materials in vitro corresponds to enhanced bone formation in vivo.…”
Section: M2 Macrophage Upregulation Is Essential During Bone Regeneration and Precedes Osteoinduction By Calcium Phosphate In Vivomentioning
confidence: 99%